A WACANA PROGRAM BANSOS UNTUK KORBAN JUDI ONLINE DALAM TINJAUAN MAṢLAḤAḤ AL-MURSALAH PERSPEKTIF WAHBAH AZ-ZUḤAILI - Afin, Muhammad; Muhammad, Azmy (Bidang Penelitian Dan Penulisan Karya Ilmiah (bp2ki) Ma'had Aly Lirboyo, 2024)
The Minister of Human Development and Cultural Affairs, Muhadjir Effendy, opened the opportunity for victims of online gambling to be included in Social Welfare Integrated Data (DTKS) so that they could receive social assistance. The victims are family members or close relatives who have been financially harmed by online gambling perpetrators. This programme sparked support and opposition from various circles. The emergence of these differing views is influenced by varying perspectives on assessing the maṣlaḥaḥ (public interest) of the program. Indeed, in the context of Islamic law, maṣlaḥaḥ can be used as a basis for legitimizing something, a method known as al-maṣlaḥaḥ al-mursalah. However, according to Wahbah az-Zuḥaili in Uṣūl al-Fiqh al-Islāmi, the measure of maṣlaḥah is not human logic but the legitimacy of syariat regarding a particular form of maṣlaḥah. According to Wahbah az-Zuḥaili, human reasoning will always differ in assessing maṣlaḥah, as seen in the differing opinions of some scholars regarding the maṣlaḥah of social assistance programs. The aim of this study is to analyze the discourse surrounding the social assistance program for victims of online gambling from the perspective of al-maṣlaḥaḥ al-mursalah, according to Wahbah az-Zuḥaili. To achieve this goal, the research method used was qualitative, with a library research approach. The data collection technique involves reviewing various literature, including classical and contemporary scholars' books, scientific articles, and other relevant sources. The results of this study indicate that this program is in line with the standards of the concept of al-maṣlaḥaḥ al-mursalah, as outlined by Wahbah az-Zuḥaili.